The pirates of Somalia [videorecording (DVD)] - Peters, Evan, 1987-; Abdi, Barkhad; Griffith, Melanie, 1957-; Pacino, Al, 1940-; Bahadur, Jay (Echo Bridge Acquisition Corp. LLC, 2018)
Based on the book "The pirates of Somalia: inside there hidden world" by Jay Bahadur.